2015
DOI: 10.3109/08923973.2015.1021357
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating effects of coenzyme Q10 and amlodipine in ulcerative colitis model in rats

Abstract: Administration of either CoQ10 or amlodipine was found to protect against acetic acid-induced colitis. Moreover, their combination was more effective than individual administration of either of them. The protective effect of CoQ10 and amlodipine may be in part via their antioxidant, anti-inflammatory and energy restoration properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Therefore, at present, it is not possible to align the multiple contradicting results of the reported clinical trials. On the other side, a plethora of literature supports the role of oxidative stress in UC and consequently justifies the use of antioxidants as a therapeutic strategy [15,27,52,54,60,[98][99][100][101][102]. Since UC is a multifactorial disease, pharmacological targeting of individual factors appears of limited use to provide effective and sustainable therapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at present, it is not possible to align the multiple contradicting results of the reported clinical trials. On the other side, a plethora of literature supports the role of oxidative stress in UC and consequently justifies the use of antioxidants as a therapeutic strategy [15,27,52,54,60,[98][99][100][101][102]. Since UC is a multifactorial disease, pharmacological targeting of individual factors appears of limited use to provide effective and sustainable therapy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are agreement with many studies. CoQ 10 significantly attenuated TNF-α level in ulcerative colitis in rats [7]. On the other hand, IL-6 and TNF-α levels were decreased by CoQ 10 application in patients with multiple sclerosis [24].…”
Section: Discussionmentioning
confidence: 92%
“…This function was accomplished either directly via protecting cellular components from free radicals or indirectly through regeneration of other endogenous antioxidants [4,5]. In experimental studies, it has been demonstrated antioxidant, anti-inflammatory and ATP-regenerative properties of CoQ 10 in various diseases such as gastric ulcer, osteoarthritis and diabetes [6,7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…TNF- α , PGE 2 , and IL-6 also play an important role in the inflammatory injury involved in UC ( Yamamoto et al, 2000 ; GomboĆĄovĂĄ et al, 2011 ; El Morsy et al, 2015 ; Sadar et al, 2016 ; El-Ashmawy et al, 2017 ; GawroƄska et al, 2017 ; Rafa et al, 2017 ; Li et al, 2018 ; Loynes et al, 2018 ). Moreover, GO analysis indicated that the proteins regulated by SNT in order to mediate its effects of UC play important roles in the pathogenesis of UC by regulating neutrophil degranulation, cell secretion, and other biological pathways.…”
Section: Discussionmentioning
confidence: 99%